Pendampingan Siswa pada Program Belajar Dari Rumah untuk Membangun Semangat Siswa Sekolah Dasar di Desa Pekalongan Kecamatan Winong Kabupaten Pati - Lestari, Indah Puji; Purnamasari, Veryliana; Purnamasari, Iin (Jurnal Inovasi Pembelajaran di Sekolah, 2021)
Pekalongan Village is a village in Winong District, Pati Regency, Central Java Province, Indonesia. The Real Work Lecture (KKN) activity which was held from January 26 to February 26, 2021, Based on data obtained, Pekalongan Village has different conditions, potentials, and problems such as problems felt by elementary, middle, and high school students who are affected by Covid -19 makes it inevitable for students to carry out learning programs from home. Real Work Lecture (KKN) is a form of community service activity that is special, because in KKN, education and teaching, research and community service are integrated into it and involve a number of students and a number of teaching staff, as well as elements of the community. Based on this, the KKN PGRI Semarang University students cannot be separated from their function as education students, they are expected to be able to distribute the knowledge or knowledge gained from the lecture bench to others. The data collection technique used in this article is a participatory approach, to provide an overview of learning assistance activities from home to build the enthusiasm of elementary school students in Pekalongan Village, Winong District, Pati Regency. So this article aims to continue to understand the phenomenon of home learning assistance that occurs holistically (whole) related to building the learning spirit of elementary school students by means of inductive analysis descriptions in the form of words and language.